DEVELOPING ACTIVITY, MOTIVATION AND FINE MOTOR ASPECT IN ATTACHING PICTURE APPROPRIATELY USING THE INTAN MODEL FOR EARLY CHILDHOOD - Atikah Rizkyareza; Aslamiah Aslamiah; Ratna Purwanti; Ishak Sin (Pendidikan Guru Pendidikan Anak Usia Dini (PG PAUD) Universitas Lambung Mangkurat, 2022)
The purpose of this study is to identify and describe teacher activity, children's activity, learning motivation and to analyze the result of children's development using the INTAN model which is a combination of the Direct Instruction model, Student Facilitator and Explaining and Mosaic Techniques. The approach used was a qualitative approach and the type of classroom action research which was conducted in second meeting with group B children of Aisyiyah Bustanul Athfal 1 Banjarmasin Kindergarten, it consists of 8 children. The data collection technique used is the observation sheet. The result of the research analysis showed that the teacher's activity gets the very good criteria. In the children's activity get the criteria of all children are active, children's development in fine motor aspect gets the criteria of all children are active and children are motivated. The result of child development at the first meeting gets the criteria of almost all children successfully developed and increased at second meeting gets the criteria of all children successfully developed. The result of this study can be used as an alternative in selecting model in developing children's cognitive abilities.